Meningkatkan Kemampuan Berjalan Melalui Latihan Menendang Bola Bagi Anak Cerebral Palsy Kelas Dasar IV di SLB Hikmah Miftahul Jannah Padang - Nofriadi - (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: This research was conduted as the researcher found a problem in the field showing that a student with Cerebral Palsy X at SLB Hikmah Miftahul Jannah Padang got difficulties to walk well. Based on the result of identification and assessment, it was figured out that child had the cild had problems to walk straight ahead, walk by following a straight line, walk by following two parallel lines, walk by following circle line and etc. therefore, the researcher tired to improve the cild’ walking ability by exercise him to kick the ball. This research was aimed at testing whether kicking the ball exercise could improve Cerebral Palsy student’s walking ability. Kata kunci: Latihan Menendang Bola, Kemampuan Berjalan, Cerebral Palsy.